Intranigral Transplantation of Fetal Substantia Nigra Allograft in the Hemiparkinsonian Rhesus Monkey - Philip A. Starr M.D.,Ph.D.; Thomas Wichmann; Craig Van Horne; Roy A. E. Bakay (Cell Transplantation, 1999)
Current clinical protocols for fetal cell transplantation for Parkinson's disease (PD) have focused on restoring dopamine in the striatum. However, there are now a number of human transplant recipients who have had robust innervation of the striatum by dopaminergic grafts (documented by positron emission tomography or by autopsy), but only a partial improvement in parkinsonian motor signs. Thus, there is a need for improved transplant strategies. In animal models of PD, there is recent evidence that restoring dopamine in the substantia nigra, instead of or in addition to the striatum, may be important to correct abnormal motor behavior. This pilot study examined the morphological features and behavioral effects of fetal dopaminergic neuronal allografts placed into the substantia nigra of three 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated hemiparkinsonian rhesus monkeys. We show that grafts can survive in host substantia nigra. Characteristics of the graft–host interface were variable. In one animal, reinnervation of host substantia nigra was observed, and this animal showed behavioral improvement in a reach-and-retrieval task.